An Empirical Study of Resource Contribution in SMEs Alliance - Kuo, W.; Lin, Chad; Hsu, G.; Huang, Y. (The Journal of Global Business Management, 2006)
SMEs operating in a rapidly changing and uncertain business environment need to form cooperative alliances in order to obtain necessary resources. However, most alliances between partners result in failure. Hence, this paper examines how different types of resource contribution affect the performance of alliances in relation to the use of dissimilar and similar resources. The results indicate that the contribution of dissimilar resources by both the focal and partner firms has a significant positive impact on alliance sustainable commitment. The results also showed that there was a positive relationship between the contribution of dissimilar resources by the partner firms and alliance performance. However, the contribution of dissimilar resources alone by the focal firms had no significant impact on alliance performance.